Postliberalism and Philosophy of Education - Michałowska, Danuta Anna (Sensus Historiae, 2022)
The aim of the paper is to present contemporary philosophical thought on education and educational policy in the context of post-liberal discourse, operating in a broad socio-cultural, political and economic space. The post-neoliberal discourse, created in the past and referring to the specific vision of the essence of humanity, which is homo neoliberalis, defined by homo oeconomicus and homo consumans, emerged as a result of a critique of the neoliberal implications for the development of the individual and society. This was a turning point for contemporary philosophy of education as well as for the perception and interpretation of the educational experience of generations of students, teachers and parents. What opens up in the context of the post-neoliberal, but also post-liberal discourse is a different perspective of a post-ideological perception of the education of young people and the formation of society as a community, functioning locally and globally, responsible for peace and the well-being of individuals and nations, as well as for maintaining the balance of the earth’s ecosystem.